Odpowiedź :
9*10⁻³)/r₁² = (3*10⁻³)/r₂ ²
mnożymy na krzyż
r₁²*(3*10⁻³)=r₂²*(9*10⁻³) || /(9*10⁻³)
(r₁²*3*10⁻³)/(9*10⁻³)=r₂ ² || 10⁻³ skraca się, 3 i 9 się skraca
r₂ ²=r₁²/3 ||√
r₂ =r₁/√3
mnożymy na krzyż
r₁²*(3*10⁻³)=r₂²*(9*10⁻³) || /(9*10⁻³)
(r₁²*3*10⁻³)/(9*10⁻³)=r₂ ² || 10⁻³ skraca się, 3 i 9 się skraca
r₂ ²=r₁²/3 ||√
r₂ =r₁/√3
(9*10⁻³)/r₁² = (3*10⁻³)/r₂ ²
r₂ ²*(9*10⁻³)=r₁²*(3*10⁻³)
r₂ ²=[r₁²*(3*10⁻³)]/(9*10⁻³)
r₂ ²=r₁²*1/3
r₂ =r₁/ √3
r₂ ²*(9*10⁻³)=r₁²*(3*10⁻³)
r₂ ²=[r₁²*(3*10⁻³)]/(9*10⁻³)
r₂ ²=r₁²*1/3
r₂ =r₁/ √3